An Objective Structured Teaching Examination (OSTE) for Generalist Resident Physicians - Elizabeth Morrison (Association of American Medical Colleges, 2005)
Abstract Introduction Using medical education literature and a focus group study, we developed and validated a 3.5-hour, 8-station objective structured teaching examination (OSTE) for medical students. Methods Twenty-three generalist residents participated in a randomized trial of a clinical teaching curriculum. Fifteen fourth-year medical students underwent 30 hours of training before developing pretest and posttest OSTEs. Students and investigators used eight case-specific, behaviorally-anchored rating scales derived from the Stanford Faculty Development Program's SFDP-26 instrument to assess teaching performance. Results Rating scale reliabilities exceeded 0.90 for all eight stations. Interrater reliabilities exceeded 0.75 for seven of eight stations. Content validity and predictive validity achieved high levels. Discussion The OSTE we developed can predictably assess student and resident comfort with clinical teaching. Other studies have suggested that taking the Clinical Teaching Perception Inventory (CTPI) will improve teaching skills.